Effects of Distracted Parenting and Housing on Juvenile's Bullying Children - Mohammed Baqer Hasan (Kufa Journal for Nursing Sciences)
Background and Aim: This study aimed to find out the effect distracted parenting and housing that lead towards Juvenile's Bullying children